(untitled) (Bangladesh Critical Care Journal, 2019)
Background: Ventilator-Associated Pneumonia (VAP) is a frequent nosocomial infection. The etiology of VAP varieswith different patient populations and types of critical care settings. Materials & methods: This prospective observational study was conducted at the Coronary Care Unit (CCU) ofIbrahim Cardiac Hospital & Research Institute from April 2016 to November 2016. Demographic details andincidence of VAP was recorded and analysed by appropriate statistical tests. Results: 52 patients required mechanical ventilation, of whom 19 (36.5%) developed VAP. 15 (78.9%) had early VAP,while 4 (21.2%) had late VAP. CPIS, Modified CPIS and APACHE II Score- all were significantly higher among thosewho developed VAP (p<0.01). The most frequent indication for intubation among those who developed VAP was type Irespiratory failure (57.9%), type II respiratory failure (15.8%) and post-cardiac arrest (26.3%). Acinetobacter (31.6%)was the commonest organism isolated on tracheal aspirate, followed by Pseudomonas (21.05%), Candida (21.05%)and Klebsiella (10.5%). Acinetobacter, Klebsiella and MRSA were the organisms isolated from tracheal aspirates ofthose with late onset VAP. Acinetobacter was mostly sensitive to Colistin, 80% of Pseudomonas is also sensitive tosame. A number of organisms were resistant to Amikacin and Imipenem. Conclusion: The commonest organism responsible for VAP in our CCU was Acinetobacter, which was largely sensitiveto Colistin. The emergence of antibiotic resistance of microorganisms causing VAP is a matter of serious concern inthis study. Regular surveillance of antibiotic susceptibility pattern is very important to prevent multi-resistant bacterialinfections. Bangladesh Crit Care J September 2019; 7(2): 73-76